The Effect Of Exercises As Standardized Resistance On The Improvement Of Abdomen and Arm Muscles According to Motor Pathway and Some Kinematical variables In Young Pole Vaulting Achievement - Mohammed, Addel (Journal of Physical Education, 2017)
The importance of the research lies in using exercises as standardized resistance to improve important arms and abdomen muscles that help the vaulter complete the correct technique and for better achievement. The problem of the research lies in vaulters incomplete arm extension during placing and pushing the pole before passing the bar as well as body extension before passing the bar and the early release of the pole causing the vaulter to touch and the bar. The research aimed at designing exercises as standardized resistance for improving abdomen and arm muscles according to motor pathway. In addition to that the researcher aimed at identifying the effect of these exercises as standardized resistance for improving abdomen and arm muscles according to motor pathway of young pole vaulters as well as identifying the effect of these exercises as standardized resistance on some kinematical variables and young pole vault achievement. The researcher hypothesized statistical difference between pre and posttests in arms’ and abdomen special strength as well as kinematical variables of pole vaulters in favor of posttests. The researcher used the experimental method. The subjects were (10) pole vaulters. The data was collected and treated using proper statistical operations. The researcher concluded that the exercises used by the experimental group improved strength faster than the exercises used by the controlling group. In addition to that, the researcher concluded increasing resistance increases the vaulter’s strength. Finally he recommended using varied exercises to improve special strength as well as the necessity of using standard resistance to improve strength and achievemen